Effect Of Food Distribiution Training On The Amount Of Food Residuals In Tehran Boali Hospital In 2010 - Seyed Jamalodin Tabibi; Mohammad Reza Maleki; Mahsa Ghazi Asgar (Tehran University of Medical Sciences, 2012)
Background and Aim: The increase of food residuals specially in hospital can lead to a decrease in food intake and customer satisfaction and also increase the cost of remedy and hospitalization. The goal of this study was to determine the effect of food service training of food staff on the amount of food residuals to improve hospital catering. Materials and Methods: This was cross sectional study. The study population consisted of staff and patients in orthopedic, chemotherapy and surgery wards and their relatives (n=130). The tools of this study were satisfaction survey questionnaire and food residual observational checklist. Questionnaires were completed by the study population and observational checklist by the researchers. Data were analysed using SPSS Software. Results: Significant difference were observed between the amount of food residual before and after personnel training (t=-5/36, p=0/001).The average amount of food remaining in the breakfast from 1/8 in pre-teaching was decreased to 0/7, at lunch from 2/09 to1/89 and in dinner time from 2/2 to 1/6. Conclusion: It seems that educational planning of personnel could increase their knowledge about their duties and weaknesses and improves quality performance which leads to customer satisfaction and hospital profitability.